Possibilities of using diversification strategy in trade enterprise operations in modern conditions - Zevenko, Dmytro; Shyshkin, Viktor; Onyshchenko, Oksana (Management and Entrepreneurship: Trends of Development, 2024)
This article is dedicated to exploring the possibilities of using a diversification strategy in the operations of a trade enterprise under modern conditions. It has been proven that diversification enables businesses to be more flexible and adapt to market changes, which enhances their competitiveness. By distributing activities across different directions, a company reduces its dependence on a single source of income and mitigates risks associated with market instability. The purpose of the article is to identify the opportunities for using a diversification strategy in trade enterprise operations in modern conditions. Methodology: A comprehensive set of general and special methods at both empirical and theoretical levels was used, such as: literature review (researching scientific papers, articles, and other sources dedicated to diversification strategies, their classification, as well as their role in the trade sector), analysis of modern trends (studying global and regional trends in trade, changes in consumer behavior, the influence of new technologies and innovations), and others. Results: It was determined that the diversification strategy provides trade enterprises with significant opportunities to strengthen their market positions, reduce risks, and ensure long-term growth. However, to use it effectively, it is necessary to carefully plan each step and consider the specifics of market conditions.JEL Classification: O1, O3, F01